A developmental perspective on personality and psychopathology across the life span. Issue 5 (18th February 2021) - Wilson, Sylia; Olino, Thomas M.
Abstract: Taking a developmental perspective, guided by core principles of developmental science and developmental psychopathology, is necessary to move the fields of personality science and psychopathology forward. Personality and psychopathology can be delineated using hierarchical models of individual differences, as evidenced by decades of converging evidence across community and psychiatric samples, countries and cultures, and ages and developmental periods. A large body of empirical research likewise documents associations between personality and various forms of psychopathology. Cross‐sectional investigations of personality–psychopathology links in samples of adults now yield diminishing returns. Prospective, longitudinal investigations that assess personality, psychopathology, and their co‐development across the life span are needed to determine their temporal ordering, capture dynamic associations over time and development, and elucidate causal origins and underlying mechanisms. We lay out a developmental framework that integrates across the developmental, personality, and psychopathology literatures in order to further understanding and guide future investigations of the nature of personality–psychopathology links.